Visualization of experience sampling method data in mental health: qualitative study of the physicians’ perspective in Germany - Schulte-Strathaus, Julia Clara Catharina; Ikegwuonu, Theresa; Schick, Anita; Wolters, Maria K.; Thurah, Lena de; Hajdúk, Michal; Kurilla, Adam; Myin-Germeys, Inez; Kiekens, Glenn; Weermeijer, Jeroen D. M.; Beames, Joanne R.; Uyttebroek, Lotte; et al. (Journal of medical internet research, 2025)
Background: Although the integration of self-monitored patient data into mental health care offers potential for advancing personalised approaches, its application in clinical practice remains largely underexplored. Capturing individuals' mental health outside the therapy room using Experience Sampling Methods (ESM) may bridge this gap by supporting shared decision-making and personalised interventions. Objective: This qualitative study investigated the perspectives of German mental health professionals regarding prototypes of ESM data visualisations designed for integration into a digital mental health tool. Methods: Semi-structured interviews were conducted with clinicians on their perceptions of such visualisations in routine care. Results: Using reflexive thematic analysis, three key findings were: (1) ESM and ESM data visualisations were seen as valuable tools for enhancing patient motivation and engagement over the course of treatment; (2) simplicity and clarity of visual formats, particularly line graphs, were preferred for usability; and (3) practical concerns, such workflow integration challenges centered on time constraints (psychotherapy session duration 50min) and need for patient psychoeducation materials, influenced perceived utility. Challenges, including the risk of cognitive overload from dense data representations (e.g., ESM mood-in-context visualisations), were raised. Conclusions: These findings underline the importance of designing digital tools that align with clinical needs while addressing potential barriers to implementation by exploring the opportunities and challenges associated with ESM visualisations.
Gesehen am 19.02.2026